Bronquitis crónica en paciente de sexo femenino de 55 años de edad. - Mindiola Salcedo, Alix Ivanna (2021)
Bronchitis is nothing more than inflammation of the bronchial tubes, the airways that carry oxygen to your lungs. This causes a cough that often contains mucus, it also causes dyspnea, shortness of breath, wheezing, and pressure in the chest. There are two types of bronchitis: acute and chronic. Most cases of acute bronchitis get better within a few days, but the cough can last for several weeks after the infection has cleared. The cost of treating ARIs is high, due to economic losses (absenteeism from work) and expenses for medicines, hospitalizations, etc. Antibiotics are prescribed in 75% of ARIs and most of the time they are unnecessary, which increases costs and bacterial resistance. It is therefore necessary to develop general strategies for the effective prevention and treatment of chronic respiratory infections (such as bronchitis), systematically evaluate the existing knowledge about ARI, disseminate it and apply it.